PENERAPAN IP VERSI 6 DALAM MEMBANGUN JARINGAN LAN - Mulyadi (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2021)
The development of computer networks is so fast along with technological developments. IPv6 is a new type of IP addressing as a successor to the IPv4 type. This study uses the type of network configuration using IPv6.The application of IPv6 in this computer network configuration is to prove that IPv6 can be used to replace IPv4 in building computer networks. The method used in this research is to conduct a trial with one of the computer network simulation software, namely Cisco Packet Tracer from a network topology that has been designed. This research was carried out through 5 stages as follows: making network design, analysis of network device requirements, conceptual analysis of configuration requirements, software network configuration and network connectivity tests. IPv6 can be used to build networks from the simplest to complex networks including LAN networks. The test results of the two network topology experiments made can be configured using IPv6 and it is proven that all computers connected to the network are all connected (100%) after the connectivity test using the ping utility. IPv6 is recommended to be used along with the increasing use of telecommunications equipment that requires an internet connection.